Transformasi Pendidikan Islam Ma’arif Nahdlatul Ulama’ Di Kabupaten Bojonegoro - Rohmad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Islamic education is a conscious effort to empower Muslims within the framework of developing Islamic civilization. Every Muslim, especially thinkers and experts in Islamic education, must feel compelled to develop and advance Islamic education. The expected Islamic education is education that is oriented towards the real needs of Islamic society today and in the future while remaining grounded in Islamic education during the heyday of Islam. This research is a qualitative research method with a descriptive analysis type of research. Results Overall the transformation of the Ma'arif NU education system was carried out in all aspects of education, such as: goals, curriculum, learning methods and models, educators and education staff, and types and management of institutions. The fact that can be seen is the growing development of Ma'arif NU educational institutions at the Elementary School (SD) / Madrasah Ibtidai'yah (MI) level, Madrasah Tsanawiyah(MTs) / Junior High School (SMP) and Madrasah Aliyah (MA) / School Senior High School (SMA) and Vocational High School (SMK). In the aspect of transformation that has been produced, it cannot be separated from a process of struggle in the effort to transform the Ma'arif Nahdlatul Ulama education system in Bojonegoro district, which then becomes an inhibiting factor, namely becauseNahdlatul Ulama has many cadres but has not been organized neatly due to the majority of members Nahdlatul Ulama figures have their own educational institutions, especially Islamic boarding schools.